The waste land : a biography of a poem - Hollis, Matthew (W. W. Norton & Company, 2023)
Renowned as one of the world's greatest poems, The Waste Land has been said to describe the moral decay of a world after war and the search for meaning in a meaningless era. It has been labeled the most truthful poem of its time; it has been branded a masterful fake. A century after its publication in 1922, T. S. Eliot's enigmatic masterpiece remains one of the most influential works ever written, and yet one of the most mysterious. In a remarkable feat of biography, Matthew Hollis reconstructs the intellectual creation of the poem and brings the material reality of its charged times vividly to life. Presenting a mosaic of historical fragments, diaries, dynamic literary criticism, and illuminating new research, he reveals the cultural and personal trauma that forged The Waste Land through the lives of its protagonists--of Ezra Pound, who edited it; of Vivien Eliot, who sustained it; and of T. S. Eliot himself, whose private torment is woven into the seams of the work. The result is an unforgettable story of lives passing in opposing directions and the astounding literary legacy they would leave behind.